2019
DOI: 10.1002/jimd.12167
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease genotype, phenotype, and migalastat amenability: Insights from a national cohort

Abstract: Fabry disease (FD) is a rare X‐linked lysosomal storage disorder caused by α‐galactosidase A (α‐Gal A) deficiency. The progressive accumulation of globotriaosylceramide results in life‐threatening complications, including renal, cardiac, and cerebrovascular diseases. The pharmacological chaperone migalastat was recently approved as an alternative to enzyme replacement therapy in patients with amenable mutations. In this article, we investigate the proportion of amenable mutations, related to phenotype, in a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The first reports on real clinical cases suggest that the beneficial long terms effects of DGJ should be evaluated carefully. In fact, a raise in AGAL residual activity has been observed in the leucocytes in patients of a Swiss cohort but regrettably, it did not correlate with a decrease in lyso-Gb3 concentration measured in dried blood spots [43].…”
Section: Pharmacological Chaperones: the Quick Path To Success Is Notmentioning
confidence: 83%
“…The first reports on real clinical cases suggest that the beneficial long terms effects of DGJ should be evaluated carefully. In fact, a raise in AGAL residual activity has been observed in the leucocytes in patients of a Swiss cohort but regrettably, it did not correlate with a decrease in lyso-Gb3 concentration measured in dried blood spots [43].…”
Section: Pharmacological Chaperones: the Quick Path To Success Is Notmentioning
confidence: 83%
“…However, the biochemical responsiveness in the GLP assay was so low that it would have been considered non-amenable according to our criteria. A recent study revealed that a patient carrying the presumed amenable variant S276N had to be switched back to ERT due to biomarker escalation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, molecular analyses using these three approaches have several roles in LD diagnosis: (1) to confirm the final diagnosis, mainly in milder and atypical cases [ 29 ]; (2) to clarify borderline biochemical results in screening and enzymatic assays, as obtained in carriers and pseudodeficiency cases (when enzyme activity is decreased but with no clinical consequences) [ 30 ]; (3) to characterize a novel gene associated with a new type of LD, such as the cases of VPS33A in MPSPS [ 21 ] and DESG1 in leukodystrophy [ 31 ]; (4) for prenatal diagnosis [ 32 , 33 ]; (5) to predict disease severity [ 34 , 35 ]; (6) for the identification of patients with variants amenable to targeted therapy [ 36 , 37 ].…”
Section: Molecular Diagnosis Advances For Lysosomal Diseasesmentioning
confidence: 99%